2017
DOI: 10.1016/j.eats.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

“Double-Row Rip-Stop” Technique for Arthroscopic Rotator Cuff Repair

Abstract: Rotator cuff repair depends on both the fixation strength of the chosen repair construct and the local healing response of the repaired tissue. Among a growing discussion surrounding the superiority of one surgical technique over another, the surgeon's ability to complete a rotator cuff repair with technical acuity in a timely manner remains paramount. Double-row repairs as well as rip-stop configurations have been proposed to limit failures found after arthroscopic rotator cuff repairs. Implementation of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Previous studies have described various rip-stop techniques; 44 - 46 however, these were different from the DRS technique. This is because the DRS technique had not only one rip-stop on the articular surface but also one on the bursal side of IST for each medial anchor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described various rip-stop techniques; 44 - 46 however, these were different from the DRS technique. This is because the DRS technique had not only one rip-stop on the articular surface but also one on the bursal side of IST for each medial anchor.…”
Section: Discussionmentioning
confidence: 99%
“…This article details a double-row suture anchor repair that may provide advantages to the surgeon over prior iterations with suture anchors (Table 2). 7, 8, 9 The suture bridge technique, for example, was developed to optimize coverage of the footprint by crossing sutures over the repaired rotator cuff 4, 7. This contrasts with the linear suture configuration of the Montgolfier double row, which remains parallel to the long axis of the rotator cuff tendon and its medial blood supply 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The Sugaya repair technique for commonly encountered delaminated tears can easily be used in combination 11 . Furthermore, to enhance fixation of the rotator cable at the leading edge of the supraspinatus, a modified Mason-Allen suture technique can be used in conjunction with this technique, similarly to a rip-stop suture 8, 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The rotator cuff suture method, which includes single-row, double-row suture, and the suture bridge techniques, enhances fixation. Recently, it has included a variety of locking sutures, such as the double-locked stitch, 2 the simple cow hitch stitch, 3 the "parachute" technique, 4 the double-row rip-stop technique, 5 the shoelace technique, 6 and the double-layer lasso loop technique. 7 For rotator cuff tears with degeneration or poor tendon quality, some studies have shown that the application of various locking ring sutures can decrease failure rate and prevent the rotator cuff from being re-torn during suture.…”
mentioning
confidence: 99%